A work-from-home wardrobe for Air-Chair : investigating (play + logic = wit) design : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand - Amdal, Karin (Massey University, 2011)
In my background as an art director in advertising, I used graphic wit as a communication tool to evoke emotion and connect with my audience; to trigger a smile in the hope of capturing their memories. The thought process behind wit is often a collision of two ideas which Koestler (1964, 35) refers to as ‘bisociation’. Heller (1991, 11) describes “wit and humour in design occur when play and logic are seamlessly intertwined”. This research project uses ( play + logic = wit ) to explore practical furniture solutions through an intuitive and conceptually driven creative practice. Instead of dressing myself for work, I dress my work chair according to mood or business of the day. This activity revealed the lack of boundaries and transition between work and home and the effects humour can play on everyday life. I have extrapolated this previous experience from 2D to 3D in the context of a collection of suits that dress Jasper Morrison’s Air-Chair. The unstructured, understated tactility and vivid colour palette of wool felt allows me to use local raw materials, to create a fabric to tailor the suits that suggests a language of three dimensional cartoon characters. In the act of dressing the chair for work, the suits invite me to an interlude of play. In a ritual transition between work and domesticity, the chair becomes a companion. The chair and I have a subtle dialogue, an experience that creates a platform to further explore lightness in everyday objects through wit.
Keywords: Graphic wit; Chair design; Working from home; Office furniture; Air-Chair